Development of the program "Method of projects" in the organization of independent work of schoolchildren at the senior stage of learning - Natalia V. Startseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper argues the use of the project method in the independent work of students in extracurricular activities and proves that it is not only an effective way to form a number of competencies, but also allows to form a high level of independence in their application. Skills of independent implementation of project activities, knowledge of methods, technologies and strategies of their implementation ensure the training of future specialists of a new generation at the secondary school stage. The article describes the developed project of extra-course activities of linguistic origination for secondary school students "Project method" in the organization of independent work of schoolchildren at the senior stage of education. It highlights all the constituents of the program: its explanatory note; educational and thematic plan; course topics; information and methodological support; methodical recommendations for the teacher; methodical recommendations for students. The relevance of the problem stated in the paper is due to the fact that the abilities developed in project activities outside of school English classes, contribute to the formation of a number of competencies.